Generation “X” and “Y” knowledge sharing behaviour: the influence of motivation and intention on non-academic staffs of higher learning institutions - Rahman, Muhammad Sabbir; Mat Daud, Nuraihan; Hassan, Hasliza (Emerald Group Publishing Ltd., 2017)
This paper aims to investigate the relationship between employee motivation and intention for knowledge sharing behaviour. Inter-Generational Differences (generations X and Y only) were assumed to moderate in the relationship between intention and knowledge sharing behaviour of non-academic staff of higher learning institutions. This research also aims to test the role of behavioural intention as mediation between motivation and knowledge sharing behaviour. Design/ Methodology/ Approach: This research tested a conceptual framework derived from widely accepted theories. This study was carried out on non-academic staffs working at the different higher learning institutions in Malaysia. Respondents from private and public higher learning institutions in Peninsular Malaysia were asked to complete a self- administered questionnaire. This research also applied confirmatory factor analysis (CFA) and structural equation modeling (SEM) to examine the proposed hypothesis of this inquiry. Findings: Results indicate that non-academic staff knowledge sharing behaviour was significantly mediated by intention between motivation and knowledge sharing behaviour relationship. More specifically, inter-generational differences (generations X and Y) play a significant moderation role between intention and knowledge sharing behaviour. Research Limitation/ Implications: The generalizability of this cross-sectional study can be strengthened by adopting a longitudinal approach in the next phase of the study. Practical Implication: The results of this research highlighted that the higher learning institutions need to institutionalize knowledge sharing behaviour among their non-academic staff (executive and nonexecutive) by facilitating knowledge sharing oriented work environment. Originality/ Value: This paper has attempted to furnish a comprehensive understanding of knowledge sharing behaviour among the non-academic staff of higher learning institutions.